Impact of Modulator Therapy on the Chronic Colonization of Lower Respiratory Tract Pathogens in Children: Data From Cystic Fibrosis Registry of Turkey - Sunman, Birce; Yalcin, Ebru; Erdal, Meltem Akgul; Sen, Velat; Baskan, Azer Kilic; Kilinc, Ayse Ayzit; Dogru, Deniz (Wiley, 2025)
Background: Modulators have revolutionized cystic fibrosis (CF) management, but their effects on respiratory pathogens remain unclear. This study evaluated changes in lower respiratory tract pathogen detection after modulator therapy in children with CF, registered in the Cystic Fibrosis Registry of Turkey. Method: This retrospective, multicenter cohort study included children receiving modulator therapy between 2020 and 2022. Chronic respiratory tract colonization rates before and after therapy were compared, along with inhaler treatments, oral steroid, azithromycin use, pulmonary function tests, and hospitalizations for pulmonary exacerbations. The cohort was stratified by age, modulator type, and lung disease severity. Changes in microbiologic data over a 1-year period were also analyzed for children not receiving modulator therapy. Results: A total of 101 children (mean age 9.95 +/- 4.44 years) were included. Following modulator therapy, respiratory cultures of 57 (56.4%) were negative. Among 32 children with chronic Pseudomonas aeruginosa (P. aeruginosa) colonization, 14 (44%) showed negative respiratory cultures after receiving modulator therapy (p = 0.039). Conversion to culture-negative status was significant for methicillin-sensitive Staphylococcus aureus (MSSA) (p = 0.022) and methicillin-resistant Staphylococcus aureus (MRSA) (p = 0.034), with ETI therapy yielding the highest conversion rates. Inhaled antibiotic use for chronic respiratory pathogens decreased significantly (p = 0.039), and spirometry parameters improved (p < 0.001). Among 1232 children not receiving modulators, 180 (14.6%) had negative respiratory cultures when examined at 1-year interval. In the same group, intermittent/chronic P. aeruginosa colonization was negative in 58 cases, while 85 developed new growth, following modulator therapy, with positivity rates rising from 16.3% to 18.5% (p = 0.030). No significant changes in other pathogen detection were observed. Conclusion: Modulators, particularly ETI, reduced respiratory pathogen detection and improved lung function in children with CF.
Keywords: CFTR modulator; cystic fibrosis; pathogen; Pseudomonas